Labour in the Board and Good Work: How to Measure and Evidence From Germany - Robert Scholz (Management revue (mrev) - Socio-Economic Studies, 2021)
Can board-level co-determination promote Good Work? Good Work can be characterised by fair income, job security, opportunities for personal development, low stress and misuse, and high-quality work equipment. Good Work is not easy to measure, in part since it has a subjective aspect. For this reason, the indicators used in this paper are derived from data on corporate and personnel structures that are supportive of Good Work. Supplementing the numerous studies that exist on the impact of works councils on Good Work, this paper highlights how board-level co-determination can also have a strong positive influence. The paper uses data from the co-determination index (Mitbestimmungsindex), a new and innovative indicator that measures the extent to which co-determination is institutionally embedded within firms. Three examples illustrate the impact of board-level co-determination on Good Work: first, on the linking of elements of Good Work with the remuneration of directors in a highly co-determined corporation; second, on the independence of the member of the management board responsible for the personnel department; and third, on the level of vocational training in the companies.
Keywords: G34; J53; M12; M53; 330; corporate governance; labour management relations; personnel management and executive compensation; training